2010
DOI: 10.1159/000319871
|View full text |Cite
|
Sign up to set email alerts
|

Local Expression of C-Reactive Protein Is Associated with Deteriorating Graft Function in Acute and Chronic Failure of Kidney Transplants

Abstract: Background: C-reactive protein (CRP) is a key molecule in inflammation and tissue homeostasis and is produced locally by renal tubular epithelial cells. Its significance of expression in contrast to expression of cytotoxic T cell (CTL) markers remains to be elucidated. Methods: By means of real-time PCR, we determined mRNA levels of CRP in 66 renal allograft biopsies with acute allograft failure and in 34 biopsies with chronic dysfunction. Results were compared to expression of CTL components (perforin, granzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…We and others have shown that markers of inflammation are associated with impaired long-term patient and graft outcome ( 35 ). Inflammation seems to correlate with endothelial dysfunction and early atherosclerotic changes in patients with chronic kidney disease (CKD) ( 6 ).…”
mentioning
confidence: 99%
“…We and others have shown that markers of inflammation are associated with impaired long-term patient and graft outcome ( 35 ). Inflammation seems to correlate with endothelial dysfunction and early atherosclerotic changes in patients with chronic kidney disease (CKD) ( 6 ).…”
mentioning
confidence: 99%
“…Blood CRP generally increases as kidney function decreases (26,36), and CRP levels are positively associated with worse outcomes and increased mortality in AKI (48,49). In the context of renal transplantation, elevated CRP levels in graft recipients associate with graft failure, and local expression of CRP mRNA in donated kidneys correlates with both acute and chronic rejection (14,31,43). There is evidence from animal models of chronic kidney disease suggesting that CRP actively increases inflammation (21,23).…”
mentioning
confidence: 99%